Efforts to Improve Employee Performance Through Interpersonal Communication in Creating an Effective Organization - Joelianti Dwi Supratiningsih (MultiTech Publisher, 2024)
In order to improve employee performance, the Swadharma Jakarta Cooperative organization uses interpersonal communication, which is more dialogical in nature and places a strong emphasis on self-disclosure. This can frequently lead to feedback and a better understanding of one another. Finding out how interpersonal communication affects worker performance at the Swadharma Jakarta Cooperative is the goal of this study. This study employs a quantitative descriptive methodology, utilizing questionnaire distribution and library data gathering approaches. 50 Swadharma Jakarta Cooperative employees were sampled using a saturated sampling strategy in this study, and the data was analyzed using a straightforward linear regression technique. The study's findings indicate that interpersonal communication at the Swadharma Jakarta Cooperative has some bearing on worker performance. It is intended that this study's findings will aid in future investigations